The Dynamics of Natural Resource and Environmental Management in Indonesia: Evaluation of Current Policies, Implementation of the Nagoya Protocol, and Sustainability Challenges - puji sri lestari (Indonesian Journal of Bioscience (IJOBI), 2025)
Biodiversity is a fundamental component for maintaining ecological balance and sustaining life on Earth. However, anthropogenic pressures such as deforestation, pollution, climate change, and overexploitation have accelerated biodiversity loss globally, including in Indonesia. This paper critically examines the dynamics of biodiversity management in Indonesia through the evaluation of current environmental policies, the implementation of the Nagoya Protocol, and the transition toward sustainable resource governance. The study incorporates theoretical insights from ecological and evolutionary biodiversity frameworks, analyzing threats and responses using recent national policies such as PES schemes, carbon taxation, and emission trading systems. Findings indicate that while Indonesia has made significant progress in integrating biodiversity protection into national development—through legal, fiscal, and conservation mechanisms—implementation challenges remain, particularly in enforcing benefit-sharing regulations under the Nagoya Protocol. Addressing these challenges requires enhanced institutional coordination, community-based participation, and international cooperation. This study contributes to the discourse on biodiversity governance and sustainable development policy in megadiverse countries.